Quality of Life in End-Stage Renal Disease Patients Undergoing Hemodialysis and Its Affecting Factors in a Hemodialysis Unit of General Hospital Denpasar - Agustina Nila Yuliawati; Pande Made Desy Ratnasari; Ni Luh Putu Satria Maharani (Borneo Journal of Pharmacy, 2023)
End-stage renal disease (ESRD) patients undergoing hemodialysis (HD) repeatedly can affect their quality of life (QOL). Its QOL value can vary according to the patient's characteristics amid health conditions that may make it difficult for them. This study aimed to analyze the QOL of ESRD patients undergoing HD and its affecting factors. This cross-sectional study was conducted in a Hemodialysis Outpatient Unit of General Hospital, Denpasar, Bali, from April to May 2021. A sample of 103 respondents was obtained by using the purposive sampling technique. Inclusion criteria were ESRD patients undergoing HD aged ≥8 years old, completing questionnaires thoroughly, and communicating well. Data was collected through the KDQOL-36 questionnaire to measure the QOL and medical records for completeness of patient identities. Data were analyzed using Spearman's ρ, η, Mann-Whitney, and an Independent sample t-test (CI 95%). Findings showed the majority of respondents were aged <60 years (75.7%), had secondary education (41.7%), were working (50.5%), were diagnosed with ESRD, and undergoing HD <3 Years (81.6%), the duration of each HD >4 hours (85.4%), three times a week (91.3%), having a BMI >29 kg/m2 (89.3%), and hypertension (42.7%). The respondents experienced major problems in their QOL on the burden of ESRD (33.50±24.64), physical (39.57±8.94), and mental component summary (52.62±10.39) dimensions. Respondent's characteristics, including education level, duration of each HD, and diagnosis with ESRD undergoing HD, contributed to their QOL (p <0.05). The patient's QOL needs to be improved through the family and health worker's support.